2007
DOI: 10.1097/01.tp.0000295742.45413.dc
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fibrin Deposition and Intravascular Thrombosis in hDAF Transgenic Pig Hearts Perfused With Tirofiban

Abstract: Improvement of heart performance and reduction of myocardial damage and intravascular thrombosis confirm a role of the GPIIb/IIIa inhibitor tirofiban for the prevention of hDAF pig heart rejection and xenograft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Although activated protein C, 59 desmopressin 60 and tirofiban 61 have shown promise in inhibiting thrombosis in ex vivo pig organ perfusion models, the results from pig‐to‐non‐human primate studies using agents including aspirin, clopidogrel, heparin, warfarin and antithrombin have been mixed 33 , 62 , 63 , 64 , 65 . This failure to consistently prolong xenograft survival may reflect progressive injury and loss of xenograft EC by non‐thrombotic mechanisms, such as cell‐mediated cytotoxicity, removing the surface required by many of these agents to exert their full effect.…”
Section: Coagulation and Thrombosis In Xenotransplantationmentioning
confidence: 99%
“…Although activated protein C, 59 desmopressin 60 and tirofiban 61 have shown promise in inhibiting thrombosis in ex vivo pig organ perfusion models, the results from pig‐to‐non‐human primate studies using agents including aspirin, clopidogrel, heparin, warfarin and antithrombin have been mixed 33 , 62 , 63 , 64 , 65 . This failure to consistently prolong xenograft survival may reflect progressive injury and loss of xenograft EC by non‐thrombotic mechanisms, such as cell‐mediated cytotoxicity, removing the surface required by many of these agents to exert their full effect.…”
Section: Coagulation and Thrombosis In Xenotransplantationmentioning
confidence: 99%
“…Eptifibatide effectively prevented platelet aggregation in an in vitro primate study and prolonged xenograft survival in a rat‐to‐guinea pig cardiac model . Tirofiban improved heart performance and reduced myocardial damage and intravascular thrombosis in pig cardiac xenotransplantation models .…”
Section: Therapeutic Options To Inhibit Platelet Activation And/or Agmentioning
confidence: 97%
“…Eptifibatide effectively prevented platelet aggregation in an in vitro primate study [100,101,103,190] and prolonged xenograft survival in a rat-to-guinea pig cardiac model [227]. Tirofiban improved heart performance and reduced myocardial damage and intravascular thrombosis in pig cardiac xenotransplantation models [228]. Thromboxane A2 is produced by activated platelets and has pro-thrombotic properties, increasing platelet aggregation.…”
Section: Othersmentioning
confidence: 99%
“…In a working-heart model with non-transgenic and human complement regulator (hDAF) pig hearts, Brandl et al [47] confirmed a certain impact for tirofiban by showing that this GPIIb/IIIa inhibitor leads to an improvement in heart performance and reduction in myocardial damage and intravascular thrombosis. Depletion of fibrinogen was equally diminished by tirofiban and hDAF, but the combination of tirofiban and GPIIb/IIIa showed additional benefits with respect to AT consumption and intravascular fibrin deposition [47].…”
Section: Glycoprotein Iib/iiia Inhibitorsmentioning
confidence: 98%